1999
DOI: 10.1136/hrt.81.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of thrombi and assessment of left atrial appendage function: a prospective study comparing transthoracic and transoesophageal echocardiography

Abstract: Objective-To compare the value of current transthoracic echocardiographic systems and transoesophageal echocardiography for assessing left atrial appendage function and imaging thrombi. Design-Single blind prospective study. Patients were first investigated by transthoracic echocardiography and thereafter by a second investigator using transoesophageal echocardiography. The feasibility of imaging the left atrial appendage, recording its velocities, and identifying thrombi within the appendage were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 22 publications
(12 reference statements)
2
44
0
2
Order By: Relevance
“…Besides, the multivariate logistic regression analysis showed that LA S res was the strongest independent predictor of the presence of LAA stasis. Conventional 2D TTE has a low sensitivity of only 3-19% for the detection of thrombi in LA and especially in LAA [10]. When the formed thrombi are absent, a dense SEC has been demonstrated to be a strong predictor of ischemic stroke [11].…”
Section: La S/sr In Prediction Of Laa Stasismentioning
confidence: 99%
“…Besides, the multivariate logistic regression analysis showed that LA S res was the strongest independent predictor of the presence of LAA stasis. Conventional 2D TTE has a low sensitivity of only 3-19% for the detection of thrombi in LA and especially in LAA [10]. When the formed thrombi are absent, a dense SEC has been demonstrated to be a strong predictor of ischemic stroke [11].…”
Section: La S/sr In Prediction Of Laa Stasismentioning
confidence: 99%
“…So far, only a few studies (3)(4)(5) have reported the detection of LAA thrombi by TTE using second harmonic imaging, and all the visualized LAA thrombi have been large (length > 1.0 cm). This was in accordance with our case, where the LAA thrombus was also large (length = 1.7 cm).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of TTE for detecting LAA thrombi is low, and only a few case reports have been described in the literature (3)(4)(5). We describe a patient with rheumatic MS and chronic AF presenting with an LA cavity mass and an LAA mass identified as a thrombus by TTE.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that increased LAA area or volume, and reduced LAA fractional area change, determined by B-mode 2D echocardiography, is associated with the presence of LAA thrombus in both AF and SR [16,22,26,27]. It should be emphasised that LAA size is increased along with LA enlargement: LAA enlargement was observed in 59% of patients with dilated LA and in only 15% of patients with normal LA size [8].…”
Section: Transoesophageal Echocardiographymentioning
confidence: 99%